2017
DOI: 10.1002/eji.201646681
|View full text |Cite
|
Sign up to set email alerts
|

Retention of Ag‐specific memory CD4+ T cells in the draining lymph node indicates lymphoid tissue resident memory populations

Abstract: Several different memory T‐cell populations have now been described based upon surface receptor expression and migratory capabilities. Here we have assessed murine endogenous memory CD4+ T cells generated within a draining lymph node and their subsequent migration to other secondary lymphoid tissues. Having established a model response targeting a specific peripheral lymph node, we temporally labelled all the cells within draining lymph node using photoconversion. Tracking of photoconverted and non‐photoconver… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
19
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(19 citation statements)
references
References 30 publications
(44 reference statements)
0
19
0
Order By: Relevance
“…26,189191 Similar as T RM isolated from non-lymphoid organs, these secondary lymphoid organ CD4 + T RM express higher levels of CD69 and lower levels of S1pr1 than their circulating counterparts. In contrast to the widely accepted notion that secondary lymphoid organs are mainly occupied by circulating T cells, antigen-specific CD4 + memory T cells residing in the draining lymph nodes are largely sessile after immunization.…”
Section: Cd4+ Trm Cellsmentioning
confidence: 96%
See 1 more Smart Citation
“…26,189191 Similar as T RM isolated from non-lymphoid organs, these secondary lymphoid organ CD4 + T RM express higher levels of CD69 and lower levels of S1pr1 than their circulating counterparts. In contrast to the widely accepted notion that secondary lymphoid organs are mainly occupied by circulating T cells, antigen-specific CD4 + memory T cells residing in the draining lymph nodes are largely sessile after immunization.…”
Section: Cd4+ Trm Cellsmentioning
confidence: 96%
“…In contrast to the widely accepted notion that secondary lymphoid organs are mainly occupied by circulating T cells, antigen-specific CD4 + memory T cells residing in the draining lymph nodes are largely sessile after immunization. 191 Further, similar CD4 + T RM cells are present in the secondary lymphoid organs of naïve specific pathogen free mice presumably due to prolonged TCR stimulation by self-antigens and microbiome-derived antigens. The population of secondary lymphoid organ CD4 + T RM expands with age.…”
Section: Cd4+ Trm Cellsmentioning
confidence: 99%
“…Tfh cells can remain for many months in the original draining lymph node where persistent antigen is likely to maintain them in an active state. These cells rapidly expand upon re‐challenge and may represent a population of lymph node resident memory cells as they can express CD69 58, 59, 60. However, this reliance on antigen suggests that these lymph node resident Tfh cells may not represent ‘true resting memory cells’.…”
Section: Memory Cd4 T‐cells Are Found Throughout the Bodymentioning
confidence: 99%
“…Along with the strong evidence that infectionor inflammation establishes Trm within NLT, there is also evidence that Trm develop within SLO (Marriott, Dutton, Tomura, & Withers, 2017; Schenkel, Fraser, & Masopust, 2014; Ugur, Schulz, Menon, Krueger, & Pabst, 2014). Utilizing parabiotic mice, Schenkel and colleagues demonstrated that a subset of viral-specific memory CD8 + T cells in SLO are in disequilibrium with the circulation and exhibit phenotypic signatures of tissue residency including CD69 expression (Schenkel etal.,2014).…”
Section: Chemokines In Memory Maintenance: Storing Memory In the Righmentioning
confidence: 97%
“…This subpopulation of antigen-specific memory CD8 + T cells were enriched in IL-15-deficient mice, suggesting distinct mechanisms of persistence compared to circulating memory CD8 + T cells. In addition to the evidence that CD8 + Trm within SLO exist, two independent groups, utilizing in vivo cell labeling via photoconversion, have demonstrated that antigen-specific memory CD4 + T cells can establish residency within SLO (Marriott et al, 2017; Ugur et al, 2014). However, it remains unclear whether constitutive chemokine signaling regulates Trm maintenance within SLO.…”
Section: Chemokines In Memory Maintenance: Storing Memory In the Righmentioning
confidence: 99%